Broadband terahertz solid-state emitter driven by Yb:YAG thin-disk oscillator - Barbiero, Gaia; Wang, Haochuan; Brons, Jonathan; Chen, Bo-Han; Pervak, Vladimir; Fattahi, Hanieh (Journal of Physics B-Atomic Molecular and Optical Physics, 2020)
We report on a table-top, high-power, terahertz (THz) solid-state emitter driven by few-cycle near-infrared pulses at 16 MHz repetition rate in gallium phosphide (GaP) crystals. Two external nonlinear multi-pass cells are used to shorten the output of a home-built, 100 W, 265 fs, 6.2 μJ Yb:YAG thin-disk oscillator, operating at 1030 nm, to 18 fs with 3.78 μJ pulse energy. The broadband spectrum of the THz driver allowed for the extension of the THz cutoff frequency to 5.7 THz at the dynamic range of 104. By employing the high-power Yb:YAG thin-disk oscillator, the low efficiency of the THz generation is circumvented, resulting in the generation of up to 100 μW, multi-octave THz pulses at 5 THz cutoff frequency in a 2 mm thick GaP crystal.
CRIS-Team Scopus Importer:2023-04-20
Keywords: broadband terahertz sources; electro-optic sampling; Kerr lens mode-locked Yb:YAG thin-disk oscillators; multi-pass cells; nonlinear broadening